2017
DOI: 10.1093/ijnp/pyx009
|View full text |Cite
|
Sign up to set email alerts
|

Z-Guggulsterone Produces Antidepressant-Like Effects in Mice through Activation of the BDNF Signaling Pathway

Abstract: Background:Z-guggulsterone, an active compound extracted from the gum resin of the tree Commiphora mukul, has been shown to improve animal memory deficits via activating the brain-derived neurotrophic factor signaling pathway. Here, we investigated the antidepressant-like effect of Z-guggulsterone in a chronic unpredictable stress mouse model of depression.Methods:The effects of Z-guggulsterone were assessed in mice with the tail suspension test and forced swimming test. Z-guggulsterone was also investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 57 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…The sucrose preference experiment was performed at day 37. The experimental mice were given the choice to drink from two bottles in individual cages, one with 1% sucrose solution and the other with water (Liu et al, ). All were acclimatized for 2 days to two‐bottle choice conditions, and the position of two bottles was changed every 6 hr to prevent possible effects of side preference in drinking behavior.…”
Section: Methodsmentioning
confidence: 99%
“…The sucrose preference experiment was performed at day 37. The experimental mice were given the choice to drink from two bottles in individual cages, one with 1% sucrose solution and the other with water (Liu et al, ). All were acclimatized for 2 days to two‐bottle choice conditions, and the position of two bottles was changed every 6 hr to prevent possible effects of side preference in drinking behavior.…”
Section: Methodsmentioning
confidence: 99%
“…In this experiment, the mice with or without LPS and/or SB treatment were given a choice to drink from 2 bottles in individual cages (one with 1% sucrose solution and the other with water) [32], and these mice were acclimatized for 2 days to this choice condition, during which the position of the 2 bottles was changed every 6 h. Once the acclimation is finished, the mice were deprived of water and food for 24 h, and on the testing day, each mouse was exposed to pre-weighed bottles for 3 h with their positions interchanged. The sucrose preference was calculated as a percentage of the consumed sucrose solution relative to the total amount of liquid intake.…”
Section: Sucrose Preference Testmentioning
confidence: 99%
“…This experiment was performed according to one of our previous studies [32]. The spontaneous activity of the mice in the OFT was evaluated in the open-field paradigm over a 5-min period.…”
Section: Open Field Testmentioning
confidence: 99%
“…Our previous studies also revealed that PDE4 modulated the development of negative emotional reactions associated with ethanol abstinence, including depression (Gong et al, 2017). Activated CREB promotes the transcription of brain-derived neurotrophic factor (BDNF), which is a potent trophic factor that maintains the morphology of neurons and mediates synaptic plasticity (ZZ Wang et al, 2013; Liu et al, 2017). The concentration of BDNF in the brain is reduced in patients with major depressive disorder, and antidepressant treatment may improve or normalize cerebral concentrations of BDNF (Sheldrick et al, 2017).…”
Section: Introductionmentioning
confidence: 99%